Impact of a Genetic Risk Score for Coronary Artery Disease on Reducing Cardiovascular Risk: A Pilot Randomized Controlled Study - Knowles, Joshua W.; Zarafshar, Shirin; Pavlovic, Aleksandra; Goldstein, Benjamin A.; Tsai, Sandra; Li, Jin; McConnell, Michael V.; Absher, Devin; Ashley, Euan A.; Kiernan, Michaela; Ioannidis, John P. A.; Assimes, Themistocles L. (Frontiers in Cardiovascular Medicine, 2017)
Purpose: We tested whether providing a genetic risk score (GRS) for coronary artery disease (CAD) would serve as a motivator to improve adherence to risk-reducing strategies. Methods: We randomized 94 participants with at least moderate risk of CAD to receive standard-of-care with (N=49) or without (N=45) their GRS at a subsequent 3-month follow-up visit. Our primary outcome was change in LDL-cholesterol between the 3-month and 6-month follow-up visits (ΔLDL-C). Secondary outcomes included other CAD risk factors, weight loss, diet, physical activity, risk perceptions, and psychological outcomes. In pre-specified analyses, we examined whether there was a greater motivational effect in participants with a higher GRS. Results: Sixty-five participants completed the protocol including 30 participants in the GRS arm. We found no change in the primary outcome between participants receiving their GRS and standard-of-care participants (ΔLDL-C: -13 vs. -9mg/dl). Among participants with a higher GRS, we observed modest effects on weight loss and physical activity. All other secondary outcomes were not significantly different, including anxiety and worry. Conclusion: Adding GRS to standard-of-care did not change lipids, adherence, or psychological outcomes. Potential modest benefits in weight loss and physical activity for participants with high GRS need to be validated in larger trials.